Quality of the Work Environment at the Office of the General Election Supervisory Agency of South Sulawesi Province - Anisah Ismawardani; Muh Darwis; Sirajuddin Saleh (Journal of Public Policy and Local Government (JPPLG), 2024)
The quality of the work environment is all the conditions, factors, and elements that affect the experience and well-being of employees in their work environment. This study aims to find out how the quality of the work environment at the Office of the General Election Supervisory Agency (BAWASLU) of South Sulawesi Province is. Therefore, the research has significant in identifying the work environment that affects the quality of the work environment. This research is qualitative, therefore, to achieve the research objectives, data collection techniques are used, namely observation, interviews and documentation. The results of this study show that all indicators used in this study are quite effective. The indicator in question is Smoothness in working quality because all employees can communicate with each other in achieving smoothness at work. The security of the quality work environment is due to the complete CCTV in every corner of the room and security carries out its duties well. The safety of the work environment is of poor quality because the work environment of BAWASLU is not in accordance with work safety standards. The cleanliness of the quality work environment is due to employee awareness and cleaning services that regularly clean. The comfort of a quality work environment is because physical comfort is enough and non-physical comfort or relationships between employees are also very good. Finally, for adequate facilities are still of poor quality because there are several facilities in each room that are still lacking, and some employees complain about it. This study presents new information by associating detailed theories and research loci different from previous research on the quality of the work environment so that it can be used as evaluation material for the research locus to improve the quality of the work environment.